2015
DOI: 10.36076/ppj/2015.18.e261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Buprenorphine on Total Intravenous Anesthetic Requirements During Spine Surgery

Abstract: Buprenorphine is a partial mu receptor agonist and kappa/delta antagonist commonly used for the treatment of opioid dependence or as an analgesic. It has a long plasma halflife and a high binding affinity for opioid receptors. This affinity is so high, that the effects are not easily antagonized by competitive antagonists, such as naloxone. The high affinity also prevents binding of other opioids, at commonly used clinical doses, to receptor sites – preventing their analgesic and likely minimum alveolar concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Tables 1 and 2 summarize the existing literature on perioperative pain management of patients on buprenorphine. Nine case reports [33][34][35][36][37][38][39][40][41] and two case series, 42,43 comprising a total of 17 cases, were identified that described perioperative course or pain management after traumatic injury among patients treated with buprenorphine for chronic pain or OUD (Table 2). In 12 of the 15 cases where buprenorphine was continued (5 case reports, plus 8 cases from the 2 case series), adequate pain control was achieved.…”
Section: Perioperative Pain Management In Patients On Buprenorphinementioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 summarize the existing literature on perioperative pain management of patients on buprenorphine. Nine case reports [33][34][35][36][37][38][39][40][41] and two case series, 42,43 comprising a total of 17 cases, were identified that described perioperative course or pain management after traumatic injury among patients treated with buprenorphine for chronic pain or OUD (Table 2). In 12 of the 15 cases where buprenorphine was continued (5 case reports, plus 8 cases from the 2 case series), adequate pain control was achieved.…”
Section: Perioperative Pain Management In Patients On Buprenorphinementioning
confidence: 99%
“…33,38,[41][42][43] Discontinuing buprenorphine was only required in three of the cases. 36,39,40 Of note, pain control in these patients required multi-modal management and titration of medication, including regional pain blocks 35 and adjustment of buprenorphine dose. 38 In the two cases where buprenorphine was discontinued 3-5 days preoperatively, it was difficult to achieve adequate pain control in the perioperative period.…”
Section: Perioperative Pain Management In Patients On Buprenorphinementioning
confidence: 99%
“…Managed on oral hydromorphone at time of discharge. Recommendation: discontinue buprenorphine.Khelemsky Y et al153 Case report A woman aged 44 years with cervical spine surgeries 5 days apart. Patient had reduced total intravenous anesthesia requirements for the latter surgery when Suboxone (8/2 mg, three times a day) was stopped after first surgery.Weaning of Suboxone preoperatively is suggested.Silva MJ et al77 Case report A man aged 53 years had one total knee arthroplasty on each knee approximately 2 years apart.…”
mentioning
confidence: 99%
“…15 Several reports have described postoperative pain despite high doses of opioid analgesics in patients on buprenorphine preoperatively. [16][17][18] However, available studies suffer from small sample sizes and lack power to detect clinically meaningful differences in pain intensity or opioid dose requirements between patients on buprenorphine and those in comparison groups.…”
mentioning
confidence: 99%
“…In contrast, buprenorphine dose dependently decreases mu-receptor availability for other full agonists at its therapeutic dose range (buprenorphine at a dose of 16 mg occupies >80% of available mu-opioid receptors), which potentially makes postoperative pain management difficult, requiring high doses of opioids 15. Several reports have described postoperative pain despite high doses of opioid analgesics in patients on buprenorphine preoperatively 16–18. However, available studies suffer from small sample sizes and lack power to detect clinically meaningful differences in pain intensity or opioid dose requirements between patients on buprenorphine and those in comparison groups.…”
mentioning
confidence: 99%